Teaching Speaking to Young Learners Using Role Play Method - Gitit I.P Wacana (Sintuwu Maroso Journal of English Teaching, 2018)
The aims of this study are: (1) to describe the use of the Role Play method in teaching speaking English for the fifth graders of MIN Poso, and (2) to determine whether the Role Play method is effective or not for the fifth graders of MIN Poso. The researcher uses descriptive method to explain the result of teaching learning process by using Role Play Method. Data are collected from observation of teaching and learning processes and documentation, and analyzed by using the theory of Landouse, Susan House, and Adam and Bidle. The results of this study are (1) English teachers in MIN Poso use four steps in teaching English speaking through Role Play method. (2) Role Play method is effectively used in teaching the fifth graders of MIN Poso to speak English because more students are active and it can increase students’ interest to speak English language.Keywords: English to young learners, speaking, role play method